Spatial coupling mechanisms of food security and regional economies: empirical examination of core-periphery dynamics in Jiangsu Province (2001–2024) - Ben, Yongqing; Zhang, Yu'e; Xu, Jinhai (Frontiers in Sustainable Food Systems, 2025)
IntroductionReconciling food security with economic development amid rapid industrialization and urbanization presents a critical global challenge. This study investigates the spatiotemporal dynamics of grain production and its spatial interaction with economic development in Jiangsu Province, China—an economically advanced region exemplifying this tension.MethodsWe integrate the Gini coefficient, concentration index, standard deviational ellipse, spatial exploratory analysis (global/local Moran's I), and a Spatial Durbin Model (SDM) to quantify spatial differentiation patterns and spillover effects.Results(1) Pronounced spatial polarization emerged: Northern Jiangsu consolidated as a High-High grain production cluster, while Southern Jiangsu evolved into a Low-Low cluster. The spatial divergence between economic and grain production centroids expanded to 125.4 km. (2) Spatial econometrics confirmed localized suppression of grain output by economic development, alongside positive spillovers to neighboring regions—validating core-periphery complementarity. Urbanization drove sown area contraction via labor migration and cropland conversion. (3) Cultivated land endowment and rural labor were fundamental pillars of food security. Industrial restructuring indirectly enhanced production through land efficiency gains.DiscussionThe findings validate core-periphery theory and reveal complex spatial spillovers. Policy prescriptions include: spatial governance mechanisms coordinating regional specialization; industrial feedback systems reinvesting economic gains into agriculture; a Technology-Driven Resource Breakthrough strategy; and institutional safeguards for cropland. This establishes a replicable paradigm for food security-economic growth synergies in developing economies.